Prolidase Could Act as a Diagnosis and Treatment Mediator in Lung Fibrosis - Turkbeyler, Ibrahim; Demir, Tuncer; Pehlivan, Yavuz; Kaplan, Davut Sinan; Ceribasi, Ali Osman; Orkmez, Mustafa; Onat, Ahmet Mesut (Springer/Plenum Publishers, 2012)
Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease with unknown etiology and pathogenesis. With high mortality risks, most of the IPF cases emerged after a damage of alveolar epithelium, where this situation stimulates the over expression of matrix components. Inflammatory process observed as a reaction to emerged damage. Prolidase as an iminodipeptidase significantly increased during the development of fibrosis. The aim of this study is to measure prolidase activity as a marker of treatment and diagnosis in an experimental lung fibrosis animal model. Thirty male Wistar rats randomly divided into three experimental groups, with ten rats in each group. Group 1, control group; group 2, bleomycin (BLM)-induced lung fibrosis group, and group 3, BLM-induced lung fibrosis treated with palosuran (urotensin-II receptor antagonist). For histopathology, the middle lobes of right lungs were embedded in paraffin, followed by fixation in 10 % buffered formalin, and evaluation of IPF was performed using the Ashcroft scoring method. Prolidase activity was determined by a photometric method based on the measurement of proline levels produced by prolidase. The fibrosis scores and the prolidase activity were significantly enhanced by BLM stimulation. The BLM + palosuran treatment decreased prolidase activity in group 3. There was a positive correlation between prolidase activity and fibrosis scores. Palosuran seems to be effective in the treatment of lung fibrosis, and prolidase activity can be used for the diagnosis and/or for management of the treatment. However, further clinical and experimental studies with animals and/or patients are needed to verify these conclusions.
Keywords: prolidase; palosuran; lung fibrosis